2011
DOI: 10.1007/978-3-642-24449-0_28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kernel-Assisted MPI Communication over Scientific Applications: CPMD and FFTW

Abstract: Abstract. Collective communication is one of the most powerful message passing concepts, enabling parallel applications to express complex communication patterns while allowing the underlying MPI to provide efficient implementations to minimize the cost of the data movements. However, with the increase in the heterogeneity inside the nodes, more specifically the memory hierarchies, harnessing the maximum compute capabilities becomes increasingly difficult. This paper investigates the impact of kernel-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Our NAS results showed that KNEM may significantly help real application performance by improving point-to-point operations while ASP experiments show that the native KNEM collective operations bring further significant efficiency. Other applications such as CPMD or FFTW have been recently studied and showed similar improvements thanks to KNEM [30].…”
Section: Applicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Our NAS results showed that KNEM may significantly help real application performance by improving point-to-point operations while ASP experiments show that the native KNEM collective operations bring further significant efficiency. Other applications such as CPMD or FFTW have been recently studied and showed similar improvements thanks to KNEM [30].…”
Section: Applicationsmentioning
confidence: 87%
“…KNEM brings significant throughput improvement to MPI communication on modern computing platforms because its single copy model reduces the CPU load, cache pollution, and memory bandwidth waste. It is already supported by most existing MPI implementations [3,5] and the use of its native interface for collective operations in Open MPI shows promising results in real world applications [30,37]. KNEM only benefits to intra-node communication, but it obviously adds a significant value to the general distributed case where both intra-node and inter-node communication are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Fast Fourier Transform on a 3D domain [39]. It employs broadcasts, scatters, and point-to-point communications [40].…”
Section: Fftmentioning
confidence: 99%